2007
DOI: 10.1074/jbc.m702358200
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Diffusion of the GABAB Receptor Is Regulated by the GABAB2 C Terminus

Abstract: GABA B (␥-aminobutyric acid, type B) is a heterodimeric G-protein-coupled receptor. The GABA B1 subunit, which contains an endoplasmic reticulum retention sequence, is only transported to the cell surface when it is associated with the GABA B2 subunit. Fluorescence recovery after photobleaching studies in transfected COS-7 cells and hippocampal neurons revealed that GABA B2 diffuses slowly within the plasma membrane whether expressed alone or with the GABA B1 subunit. Treatment of cells with brefeldin A reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…Recently, there is increasing evidence in support of rapid GABA B receptor recycling (11), constitutive endocytosis (9), and lateral diffusion of these receptors in the cell membrane (10). Why these studies reach different conclusions is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there is increasing evidence in support of rapid GABA B receptor recycling (11), constitutive endocytosis (9), and lateral diffusion of these receptors in the cell membrane (10). Why these studies reach different conclusions is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports indicate that agonist activation of GABA B receptors may promote internalization and/or rapid recycling (10,11,18). To address the topic of GABA B receptor trafficking, prior studies have used various techniques to monitor receptor movement, including: receptor biotinylation (8,9); antibody labeling of extracellular GABA B receptor epitopes on live cells (9); as well as fluorescence recovery after photobleaching (FRAP) (10). These methods have therefore relied on the use of relatively large reporter molecules, such as antibodies.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Neither native nor recombinant GABA B Rs are G protein-coupled receptor-dependent kinase substrates, and they do not undergo agonist-induced internalization (9, 10). They do, however, display constitutive endocytosis (11), and it has been proposed that they undergo both very rapid endocytic recycling (12, 13) and membrane lateral diffusion (14). …”
Section: Introductionmentioning
confidence: 99%
“…Examination of the dynamic lateral diffusion of GABA B receptors at the cell surface revealed restricted mobility of GABA B2 . After activation by baclofen, levels of the mobile fraction were significantly increased (Pooler and McIlhinney, 2007). Furthermore, by using single-molecule analysis of fluorescently labeled GPCR revealed that larger oligomers of GABA B receptor were prevalently organized into ordered arrays (Calebiro et al, 2013).…”
Section: Gabab Receptor Cell Surface Expression and Localizationmentioning
confidence: 99%